A randomised, multicentre open-label phase II study to evaluate the efficacy, tolerability and pharmacokinetics of oral vinorelbine plus cisplatin versus intravenous vinorelbine plus cisplatin in Chinese patients with chemotherapy-naive unresectable or metastatic non-small cell lung cancer - Yang, Yunpeng; Chang, Jianhua; Huang, Cheng; Zhang, Yiping; Wang, Jie; Shu, Yongqian; Burillon, Jean Philippe; Riggi, Marcello; Petain, Aurélie; Ferre, Pierre; Liang, Ying; Zhang, Li (Journal of Thoracic Disease, 2019)
Background: A phase II study to evaluate the efficacy, tolerability and pharmacokinetics of oral or intravenous vinorelbine (VRL) plus cisplatin (CDDP) in Chinese patients with non-small cell lung cancer (NSCLC). Methods: One hundred and thirty-one patients were randomised to oral VRL 60 mg/m2 (arm A) or intravenous VRL 25 mg/m2 (arm B) on days 1 and 8, plus CDDP 80 mg/m2 on day 1 (both arms). VRL was increased to 80 mg/m2 (arm A) or 30 mg/m2 (arm B) in cycles 2–4 in the absence of toxicity. Primary efficacy endpoint was objective response rate (ORR). VRL pharmacokinetics was evaluated for possible drug-drug interactions with CDDP. Results: ORR was 25.8% in arm A and 23.1% in arm B. Disease control rate was 72.7% in arm A, 72.3% in arm B. Median overall survival was 16.1 months in arm A and 19.0 months in arm B. Median progression-free survival was 4.6 months in arm A and 4.9 months in arm B. Forty-three point nine percent and 86.2% of patients had grade 3/4 neutropenia in arms A and B, respectively; incidence of febrile neutropenia was low (6.1% and 9.2%, respectively). Frequency of grade 3/4 non-haematological adverse events was also low. VRL pharmacokinetics was not affected by co-administration of CDDP. Conclusions: Oral and intravenous VRL in combination with CDDP is effective and well-tolerated in Chinese patients with advanced NSCLC. VRL pharmacokinetics is unaffected by CDDP co-administration. Oral VRL could be an effective alternative to intravenous VRL as a first-line treatment for NSCLC, as it optimises treatment convenience while maintaining high efficacy.